Effect of Dietary Selenium Supplementation on Morphology and Antioxidant Status in Testes of Goat - Iqra Bano; M. Malhi; S.A. Soomro; Safia Kandhro; Muhammad Awais; Seema Baloch; Saba Perveen; Hira Sajjad (Journal of Basic & Applied Sciences, 2018)
The fitness of animal has an enormous influence on its reproductive capability, nowadays feeding of microelements is practiced in many feed formulations because micro-nutrient possesses strong influence on animal’s reproductive ability. The male generative zone produces spermatozoa which needs a little number of free radicals for the maturation as well as for smooth fertilization. Whereas the raised level of these free radicals disturbs the entire process of sperm formation and also lead to infertility. The Selenium is a micro nutrient which naturally possess some enzymes and selenoproteins which diminish manufacture of unnecessary free radicals by acting as an antioxidant. Subsequently, it protects male gamete from destruction triggered by oxidative stress. Selenium also assistance in maintenance of semen quality by declining construction of atypical spermatozoa. Additionally, some studies have revealed that it possesses striking influence on both gross and histological characteristics of male reproductive organ, feeding this mineral improved circumference, size, the mass of the testis and speed up sperm construction by means of having a solid effect on seminiferous tubules histology. Hence, selenium shortage can cause infertility and further reproductive syndromes.